Trade Tensions, Global Value Chains, and Spillovers : Insights for Europe - Huidrom, Raju (Departmental Papers; Departmental Paper ;, 2019)
Europe is deeply integrated into global value chains and recent trade tensions raise the question of how European economies would be affected by the introduction of tariffs or other trade barriers. This paper estimates the impact of trade shocks and growth spillovers using value added measures to better gauge the associated costs across European countries.